PERANCANGAN PANTI WERDHA PRIA DAN WANITA DIKOTA BELITUNG DENGAN PENDEKATAN ARSITEKTUR PERILAK - NINDA OKTALIA; ANGGRAENI DYAH; PUTRI SURYANDARI (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Nursing homes are residential areas and facilities where elderly people gather and carry out activities therein with the help of organizations to help and meet their needs during their old age, so housing facilities are created that are adapted to their needs and behavior. Aik Seruk in the city of Belitung was chosen to be the location of the land used for designing. Considering that the area is a residential and agricultural area which is certainly suitable to be used as a Nursing Home area where tranquility is needed away from the hustle and bustle of the city.